Aplicação das ondas eletromagnéticas em rádio FM e a importância da propagação dessas ondas nos meios de telecomunicação - FERREIRA FILHO, Ubaldo Nahum (2022)
The study had as fundamental principle to realize an application of the electromagnetic waves in an FM radio and the importance of the propagation of these waves in the means of telecommunication. For this, an FM radio transmitter was built in the range of 87,5MHZ to 108MHZ to show the relevance of the application of electromagnetic waves in this small device and at the same time, consider the utility in telecommunications that in a broad way is essential for the development of technologies. In this way the basic equations of electromagnetic theory have own basis in numerous applications of great utility for the scientific and technological development. Thus the work proposes to develop a study of the layers of the atmosphere to explain how the transmission of electromagnetic waves occurs, enabling communication and possible transmissions in digital TV sets and other devices of a technological nature, such as cell phones and GPS. It is also worth considering that the electromagnetic wave occupies an enormous range of values of wavelength in the electromagnetic spectrum and to analyse each band of it, it is necessary a detailed study of each band as well as the innumerable applications that can be observed in different scientific branches. However, this work addresses only the FM radio transmitter to the application of a small band of the spectrum in order to show the relevance for the communication and technological development, with emphasis on the basic equations of Mawxell.